PUBLIC SERVICES AT HALUOLEO AIRPORT TOWARDS SOCIETY 5.0 - Joko Tri Brata; Rahmisyari Rahmisyari; Mustaking Mustaking (Pusat Riset dan Inovasi Nasional, 2023)
The development of a territory requires adequate and accountable transportation services. The objectives of this study are to determine (1) how people's perceptions of public services at Haluoleo Airport align with the Society 5.0 concept and (2) supporting factors for public services at Haluoleo Airport in the Society 5.0 era. The research method used was a qualitative research technique with an emphasis on a sample of 70 airplane passenger respondents. The results of the study concluded that: (1) Public servants at HaluoleoKendari Airport, with indicators that: communication is already good, participation still needs to be increased, officials must be able to direct, officers must provide quick action, officers are on time, officers are friendly enough, followed by comfortable airport facilities and officers who are attentive; (2) The factors that affect the quality of service at Haluoleo Airport are mainly in terms of human resources, and the main weaknesses are related to professionalism and competence at the educational level, which still needs improvement, even though the current implementation of organizational culture is quite good because there are guidelines for the organization and sufficient leadership. To improve service, employee responsiveness is still needed to hear various complaints, aspirations, and expectations of airport service users, and officials must be informative so that information that should be conveyed to airport service users reaches airport service users, as well as efforts to improve inter-organizational coordination at the airport.